Chromosome-level genome assembly of the pine wood nematode carrier Arhopalus unicolor - Xiangying Zou; Liqiong Zeng; Xingzao You; Jinghui Zhong; Chensheng Tang; Zhaofei Zheng; Xiaochun Lin; Biaoqiang Zhang; Xinliang Zhang; Yu Fang; Yanli Sun; Shouping Cai; et al. (Scientific Data)
Abstract Arhopalus unicolor is a carrier of the pine wood nematode (PWN), which causes pine wilt disease, killing pine trees and causing considerable economic and environmental losses. While the A. unicolor mitochondrial genome has been published, a high-quality genome assembly and annotation of A. unicolor is not yet available. To address this, we assembled a chromosome-level reference genome assembly of A. unicolor with a combination of Illumina, PacBio, and Hi-C sequencing technologies. The final genome size was determined to be 1268.11 Mb, with a GC% of 32.44%, and the scaffold N50 value was 19.30 Mb. A total of 98.77% of the assembled sequences mapped to 10 pseudochromosomes, and BUSCO analysis revealed high completeness, with 97.15% gene coverage. Furthermore, the genome contains 71.74% repeat elements and encompasses 16,450 predicted protein-coding genes. This genome sequence of A. unicolor will be a valuable resource for understanding the genetics and evolutionary history of this species and for developing effective management strategies for this PWN carrier.